Chlorophyll-a monitoring in reservoirs on open source geospatial platforms: Case study – public water supply sources in the São Paulo Metropolitan Region (RMSP) (Research, Society and Development, 2025)
The efficient management of water resources is a global challenge that demands innovative approaches to monitoring water quality. This objective study explores the application of Google Earth Engine (GEE) to monitor chlorophyll-a in dams operated by Sabesp, using images from the Sentinel-2 satellite. It was estimated using the OC2_490 algorithm and the Tri-band index (TBDO) in eutrophic environments. The results showed seasonal variations, influenced by climatic factors and human activities. The methodology used enabled a detailed analysis of variations in chlorophyll-a, essential for evaluating phytoplankton dynamics in dams. Although some representations present missing data, others provided robust information, revealing seasonal patterns, with notable peaks in chlorophyll-a in June, possibly related to algal blooms. The GEE platform, with its cloud processing capability, has been declared an effective tool for large-scale continuous water quality monitoring.